METACOGNITIVE STRATEGIES IN STUDENT’S READING COMPREHENSION - Nur Aisah; Lucky Rahayu Nurjamin (Institut Pendidikan Indonesia Garut, 2021)
The aim of this study is to find out the process of using metacognitive strategies applied by introvert student in reading comprehension. This study used qualitative research in terms of descriptive study. In collecting the data, there were two instruments applied; interview, especially semi-interview because it was to find out the problem naturally and not only focus on taking notes during the research and the second instrument was observation. The setting of this study was conducted in outdoor room and the participant was an introvert student of fifteen years old in non-formal education. The study results were the introvert student used metacognitive strategies with three stages in the process of reading, they were planning before reading, monitoring during reading and evaluating after reading, it was removing shortcomings in reading especially in pronunciation and vocabulary, the introvert student thought what she was thinking to maximize her own productivity in reading, she asked herself what she already knew to focus her thinking of reading, and she evaluated what she has carried out in the process of reading, the introvert student fostered forethought and self-reflection in the process of reading so that she became aware of how she learned and evaluated and adapted skills to increase reading comprehension.